Female Patients With Sleep-Disordered Breathing Display More Frequently Heart Failure With Preserved Ejection Fraction - Lebek, Simon; Hegner, Philipp; Tafelmeier, Maria; Rupprecht, Leopold; Schmid, Christof; Maier, Lars Siegfried; Arzt, Michael; Wagner, Stefan (Frontiers in Medicine, 2021)
Objective: Sleep-disordered breathing (SDB) is a widespread disease that is often associated with heart failure (HF) with preserved ejection fraction (HFpEF). HFpEF is more frequent in women than in men, but detailed pathomechanisms remain unclear. We investigated HFpEF in women and men in a high-risk cohort with SDB monitoring. Methods and Results: Three hundred twenty-seven patients (84.4% men) undergoing elective coronary artery bypass grafting were prospectively subjected to SDB monitoring, and an apnea–hypopnea index (AHI) ≥15/h defined SDB. HF was classified according to current guidelines. HFpEF was significantly more frequent in SDB patients compared to those without SDB (28 vs. 17%, P = 0.016). This distribution was driven by an increased frequency of HFpEF in female SDB patients (48% vs. only 25% in male, P = 0.022). In accordance, female patients with SDB exhibited significantly more impaired diastolic left ventricular filling compared to men (echocardiographic E/e′). In contrast to men, in women, minimum oxygen saturation (O2min, measured by polygraphy, R2 = 0.470, P < 0.001) and time of oxygen saturation <90% (R2 = 0.165, P = 0.044) were significantly correlated with E/e′. Moreover, the correlation between O2min and E/e′ was significantly different in women compared to men (P < 0.001). Intriguingly, this association remained independent of clinical covariates in women [age, body mass index, systolic contractile dysfunction, diabetes mellitus, and glomerular filtration rate (GFR), R2 = 0.534, P = 0.042, multivariate regression analysis]. Since angiotensin II signaling has been mechanistically linked to HF, we measured protein expression of its cleavage enzyme ACE2 in human right atrial appendage biopsies (Western blot). Intriguingly, we found a significantly decreased ACE2 expression preferentially in women with SDB (2.66 ± 0.42 vs. 4.01 ± 2.47 in men with SDB, P = 0.005). In accordance, left ventricular mass index was significantly increased in women with SDB compared to women without SDB. Conclusion: In patients with SDB, HFpEF and diastolic dysfunction were more frequent in women compared to men. In contrast to men, the severity of SDB was associated with the degree of diastolic dysfunction in women. These insights might help to find sex-specific therapies for patients with sleep-disordered breathing and heart failure. Clinical Trial Registration: Unique identifier: NCT02877745, URL: http://www.clinicaltrials.gov.